Neuromuscular control adaptations in elite athletes: the case of top level karateka - Sbriccoli, P.; Camomilla, V.; Di Mario, A.; Quinzi, F.; Figura, F.; Felici, F. (European Journal of Applied Physiology, 2010)
This paper aimed at investigating the neuromuscular response of knee flexor and extensor muscles in elite karateka and karate amateurs (Amateurs) during isokinetic knee flexion/extensions and during the execution of a front kick (FK). Surface electromyograms (sEMG) were recorded from the right vastus lateralis (VL) and biceps femoris (BF) muscles with a four-array electrode during maximal isometric knee flexion and extension (maximal voluntary contraction), during isokinetic contractions (30°, 90°, 180°, 270°, 340°, 400°/s), and during the FK. The level of VL and BF agonist (ago) and antagonist (ant) activation during the isokinetic and FK protocols was quantified through normalized sEMG root mean square value (%RMSago/ant-ISOK/FK). VL and BF average muscle fiber conduction velocity (CV) was computed for isokinetic and FK. Isokinetic flexion and extension torques and knee angular velocity during FK were also assessed. Analysis of variance was used to test the effect of group, angular velocity, and task on the assessed variables (P < 0.05). Elite karateka showed higher isokinetic knee flexion torque when compared with Amateurs. For all angular velocities, VL and BF %RMSant-isokinetic were lower in elite karateka, while their BF-CVisokinetic BF-CVfront kick and BF %RMSant-front kick values were higher. For VL and BF, %RMSago-front kick was lower than %RMSago-isokinetic in both groups. Elite karateka demonstrated a typical neuromuscular activation strategy that seems task and skill level dependent. Knee flexion torque and CV results suggest the presence of an improved ability of elite karateka to recruit fast MUs as a part of training induced neuromuscular adaptation.